Snow cover in support of development of winter tourism activities in Muntele Băișorii resort - Ovidiu GACEU; Luca ZARRILLI; Maria GOZNER; Anca-Cristina POP (Editura Universităţii din Oradea, 2015)
The paper presents the characteristics of snow cover in Muntele Băişorii resort expressed on the basis of analyzing the data from meteorological observation from Băişoara station during 1961-2007 and processed on the basis of classic methodology used in climatological studies. Analyzing the values of the main parameters characterizing the snow cover was found that it enables and promotes winter tourism activities, that is why we have proposed new types of winter tourist activities such as ski touring, which would help diversify and increase the tourist flow in the resort.